Microplate Methods for Measuring Phenolic Content and Antioxidant Capacity in Chickpea: Impact of Shaking - Joel B. Johnson; Janice S. Mani; Mani Naiker (Engineering Proceedings, 2023)
Microplate-based methods are commonly used to conduct spectrophotometric-based assays on large batches of sample extracts as they allow much greater throughput compared to traditional benchtop methods. However, many reported methods have not undergone a thorough method development/optimisation process; thus, the significance of maintaining certain parameters and procedures is often unknown. This study investigated the importance of plate shaking prior to the absorbance measurement step in two common assays: total phenolic content (TPC) measured using the Folin–Ciocalteu method, and total antioxidant activity measured using the Ferric Reducing Antioxidant Power (FRAP) method. A comparison was conducted on 36 methanol extracts of chickpea (Cicer arietinum) kernel, which had TPCs ranging from 43 to 111 mg GAEs (gallic acid equivalents)/L and FRAP values ranging from 25 to 67 mg TE (Trolox equivalents)/L. The absorbance of the samples was measured before and after the plate was shaken (300 s); each sample was analysed in duplicate. For the TPC, the unshaken and shaken absorbance values showed a high correlation with one another (R2 = 0.990); however, a paired samples t-test demonstrated a significant increase in absorbance after shaking (p < 0.001; mean increase of 10.6%). Similarly, the unshaken and shaken absorbance values for FRAP showed a strong correlation (R2 = 0.973), but again the shaken absorbance values were significantly higher (p < 0.001, mean increase of 12.1%). This demonstrates the importance of plate shaking for ensuring the complete reaction of the well contents prior to measuring their absorbance values. Furthermore, it highlights the need to closely follow the specified procedure when attempting to replicate or set up a microplate-based spectrophotometric method from the literature.